Primitive Neuroectodermal Tumor/Ewing Sarcoma Presenting with Pulmonary Nodular Lesions - Selvi Asker; Fuat Sayir; Gulay Bulut; Aysel Sunnetcioglu; Selami Ekin; Alpaslan Yavuz (Case Reports in Oncological Medicine)
Primitive neuroectodermal tumors (PNETs) and Ewing sarcoma (EWS) belong to the same family of malignant, small, round cell neoplasms of soft tissue or bone origin. EWS-PNETs that arise in the lung parenchyma involvement are extremely rare in adults. A case of a 32-year-old male presenting with chest pain and diffuse pulmonary nodules on chest X-ray and diagnosed with Ewing sarcoma-PNETs will be presented here.